Review of John Polkinghorne's Science and theology: an introduction - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 2000)
John Polkinghorne is well known as a leading figure relating theology to physics. Confronted with the claim that science and theology are inevitably at odds with each other, Polkinghorne replied, and here demonstrates, that "You don't have to commit intellectual suicide to be a believer."
Science and theology: an introduction - review
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: science; physics; theology; mind in nature; cosmology